Overview of Intra Anesthesia Hemodynamic Status in Patients with Spinal Anesthesia Action - Rahman; Lintang Suryani, Roro; Kemal Firdaus, Eza (Java Nursing Journal, 2024)
Background: Hemodynamic observation during spinal anesthesia is necessary to assess the status of a patient's cardiovascular system. Hemodynamic decline is one of the most common acute complications that can occur in spinal anesthesia. Purpose: to determine the description of intra-anesthesia hemodynamic status in patients with spinal anesthesia at Morowali Hospital. Methods: This research design uses descriptive design. The sampling technique with total sampling obtained 85 patients who performed spinal anesthesia. The research instrument contains monitoring the patient's vital signs including systole blood pressure, diastole, pulse frequency, and MAP value. Results: The age of patients is most with early adulthood at 33 (38.8%) and the least with the elderly category at 2 (2.4%). The gender of the respondents was mostly female with 51 (60%). The type of surgery with the majority with major surgery amounted to 51 (60%) and the most ASA status with ASA 2 amounted to 74 (87.1%). Conclusion: hemodynamic status based on systole and diastole blood pressure in the normal category was 63 (74.1%), based on pulse frequency the majority with normal status was 58 (68.2%), based on MAP values the majority with normal was 53 (62.4%).